2007
DOI: 10.1016/j.pain.2006.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Catechol- O -methyltransferase inhibition increases pain sensitivity through activation of both β2- and β3-adrenergic receptors

Abstract: Catechol-O-methyltransferase (COMT), an enzyme that metabolizes catecholamines, has recently been implicated in the modulation of pain. Our group demonstrated that human genetic variants of COMT are predictive for the development of Temporomandibular Joint Disorder (TMJD) and are associated with heightened experimental pain sensitivity (Diatchenko et al. 2005). Variants associated with heightened pain sensitivity produce lower COMT activity. Here we report the mechanisms underlying COMT-dependent pain sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
201
2
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 256 publications
(226 citation statements)
references
References 72 publications
(78 reference statements)
10
201
2
13
Order By: Relevance
“…Based on findings in animal models, Nackley et al (9) proposed that COMT inhibition results in increased pain sensitivity via AR activation. Additional evidence incriminates dysfunctional ARs in the pathogenesis of chronic painful conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on findings in animal models, Nackley et al (9) proposed that COMT inhibition results in increased pain sensitivity via AR activation. Additional evidence incriminates dysfunctional ARs in the pathogenesis of chronic painful conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This plasticity may compromise homeostasis (8). Investigations in animals demonstrated that low COMT activity leads to increased pain sensitivity via AR activation (9). The aim of the present study was thus to correlate ␣-AR and ␤-AR gene polymorphisms with the presence of FM and with different domains of the FM syndrome.…”
Section: Conclusion Ar Gene Polymorphisms Are Related To the Risk Ofmentioning
confidence: 91%
“…У пациентов с невропатиче-ской болью заболеваемость мигренью, фибромиалгией, тре-вожно-депрессивными расстройствами значительно выше, чем у пациентов без невропатической боли [13][14][15]. В свою очередь у пациентов с мигренью коморбидными являются следующие заболевания: эпилепсия, синдром раздраженного кишечника, язвенная болезнь желудка, бронхиальная астма, аллергия, тревожные и депрессивные расстройства [16,17]. Пациенты с фибромиалгией чаще болеют гипертонической болезнью, синдромом раздраженного кишечника, остеоарт-ритами, тревожными и депрессивными расстройствами [13].…”
unclassified
“…Современные данные о связи между полиморфизмом генов и особенностями болевой чувстви-тельности подтверждают высказанное предположение. В ча-стности, показано, что функциональный полиморфизм в ге-не, кодирующем синтез фермента catecholamine-O-methyltransferase (COMT), может изменять метаболизм катехолами-нов и в значительной мере влиять на характер болевой чувст-вительности [16,19]. Доказано, что гаплотипы с низкой чув-ствительностью к боли обеспечивают более высокий уровень ферментативной активности COMT по сравнению с гаплоти-пами, ассоциированными со средней и высокой болевой чув-ствительностью.…”
unclassified
See 1 more Smart Citation